Dog-walking in dense compact areas: The role of neighbourhood built environment. (January 2020) - Koohsari, Mohammad Javad; Nakaya, Tomoki; McCormack, Gavin R.; Shibata, Ai; Ishii, Kaori; Yasunaga, Akitomo; Liao, Yung; Oka, Koichiro
Abstract: There is a dearth of evidence about how high-density living may influence dog-walking behaviour. We examined associations between neighbourhood built environment attributes and dog-ownership and dog-walking behaviour in Japan. Data from 1058 participants were used. The dog-ownership was 18.8%. All neighbourhood built attributes (excluding availability of parks) were negatively associated with dog-ownership. Among dog-owners, these same attributes were positively associated with any dog-walking in a usual week and with achieving 150-min per week of physical activity through dog-walking alone. These findings provided evidence on the importance of neighbourhood built environment attributes on dog-ownership and dog-walking behaviour in dense and compact areas. The urban design and public health implication of these findings is that the built environment attributes in high-density living areas may have different impacts on dog-ownership and dog-walking: while living in a walkable neighbourhood may not be conducive to dog-ownership, it may support dog-walking in such areas. Programs targeting dog-owners in high-density areas might be needed to encourage them to walk their dogs more. If successful, these programs could contribute to higher physical activity levels among dog-owners. Highlights: It is unclear how high-density living may influence dog-walking. Living in dense compact areas was not associated with dog-ownership, but was associated with dog-walking. The built attributes in high-density living areas have different impacts on dog-ownership and dog-walking.